Obtaining Ambient‐Stable MXene Ti3C2Tx through Avoidance of Surface Oxidation Active Sites. Issue 24 (28th July 2022) - Li, Xuesong; Xue, Ni; Yao, Qian; Han, Liuyuan; Zhao, Xiangyan; Li, Bo; He, Tao; Tao, Xutang
Abstract: As the quintessential representation of MXenes, Ti3 C2 T x has attracted widespread scientific interest and has demonstrated unparalleled potential in various applications. However, Ti3 C2 T x has always been subject to its ambient instability, which deteriorates the intrinsic properties and limits the practical applications. The mechanism responsible for oxidative degradation of Ti3 C2 T x has remained elusive, and the subsequent improvement of the preparation for ambient‐stable Ti3 C2 T x is still a challenge. In this paper, the ambient instability of Ti3 C2 T x is found to be attributed to the presence of many oxidation active sites on the surface, the formation of which is highly correlated with the enrichment of etching by‐products (AlF x or Al(OF) x ). Based on the above findings a slow‐speed etching method is designed, using tetramethylammonium hydroxide as a separate etching‐agent, to avoid adsorption of fluorine‐containing by‐products during etching. The prepared high‐quality Ti3 C2 T x flakes exhibit excellent ambient stability even after 4 months of dispersion in water, unlike conventional aqueous Ti3 C2 T x dispersions that can only be kept for a few days. The intrinsic stability allows Ti3 C2 T x to avoid its decomposition in seawater desalination, and it exhibits superior desalination ability with a maximum reduction of 62.2% in Na + permeability and a maximum increase of 300% in water flux. Abstract : This work reveals the root cause of the ambient instability of MXene Ti3 C2 T x, identifying a microscopic origin of oxidation active sites. Simultaneously, an effective method to prepare stable Ti3 C2 T x is proposed, representing a considerable step forward in obtaining long‐term stable Ti3 C2 T x flakes as well as facilitating practical applications.